2003
DOI: 10.1128/mcb.23.21.7648-7657.2003
|View full text |Cite
|
Sign up to set email alerts
|

Miz1 Is Required for Early Embryonic Development during Gastrulation

Abstract: Miz1 is a member of the POZ domain/zinc finger transcription factor family. In vivo, Miz1 forms a complex with the Myc oncoprotein and recruits Myc to core promoter elements. The MYC (or c-MYC) gene and two of its relatives, MYCL and MYCN, are causally involved in the genesis of a wide variety of human tumors (32). c-MYC encodes a transcription factor (Myc) that can both activate and repress transcription. Myc activates transcription as part of a heterodimeric complex with the Max protein (1, 23). The complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 48 publications
4
57
0
1
Order By: Relevance
“…Controversially, Adhikary et al (2003) reported that Miz-1 is required for early embryonic development during gastrulation. Similarly, Ziegelbauer et al (2004) reported that the loss of Miz-1 by RNA interference caused cells to accumulate in G1 and led to inhibition of cell proliferation in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Controversially, Adhikary et al (2003) reported that Miz-1 is required for early embryonic development during gastrulation. Similarly, Ziegelbauer et al (2004) reported that the loss of Miz-1 by RNA interference caused cells to accumulate in G1 and led to inhibition of cell proliferation in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Myc represses the cell cycle inhibitors p21Cip1, p15Ink4b and p57Kip2 via binding to Miz-1 (Adhikary et al, 2003;Seoane et al, 2002;Staller et al, 2001). A recent paper by Fasano et al reveals that Bmi-1 induced inhibition of the p21Cip1 is essential for neural stem cell self-renewal during development (Fasano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The murine miz-1 gene is essential during early development; homozygous deletion of miz-1 causes massive apoptosis of ectodermal cells at E7.5 during gastrulation (Adhikary et al 2003). The phenotype of miz-1 DPOZ mice is less severe, but mice still die late in embryogenesis .…”
Section: Normal Developmentmentioning
confidence: 99%
“…In vivo, MIZ-1 is critical for suppression of CDKN1A in response to the tumor promoter TPA, during skin carcinogenesis (see below), and for repression of CDKN1A in response to endogenous DNA damage during recombination of T-cell receptors. Similarly, the CDKN1C ( p57Kip2) gene is a direct target of MIZ-1 and MYC represses CDKN1C in a MIZ-1-dependent manner during lymphomagenesis (Adhikary et al 2003;van Riggelen et al 2010).…”
Section: Transcriptional Repression By Myc Via Interaction With Miz-1mentioning
confidence: 99%